Methodology of Competences Management Assuming the Cuban Norm about Management of Human Capital - Santos, Armando Cuesta (Review of Business Management, 2011)
An applied research conducted in eight Cuban companies which follow the approach of skills in strategic management of human resources according to the standard Cuban CN: 3000-3002:2007 on human capital management, seeking a superior performance to higher productivity. It sought to manage the connection of individual work with the responsibilities for the strategic organizational performance. As a result we have obtained a metodology to manage the various skill levels expressed in this companies, which acceptance of the competence concept in the position is fundamental in the NC mentioned. Presenting this methodology for performance management competence is the mais purpose of this article. Key words: Management methodology. Work competences. Strategy.